Spontaneous rupture of primary splenic angiosarcoma: A case report - XU, BOTAO (Oncol Lett, 2015)
Primary angiosarcoma of the spleen is an extremely rare malignant neoplasm of vascular origin that often has a poor prognosis. The majority of cases presents with splenic rupture and hemorrhage. The present study retrospectively analyzed the case of 77-year-old female who presented with diffuse abdominal pain and distension. During laparotomy, a huge actively bleeding spleen was identified and a splenectomy was performed. Since an accurate diagnosis could not be achieved by abdominal computed tomography, a pathological examination was performed. The patient and the family refused post-operative adjuvant chemotherapy and radiation therapy. The patient succumbed to uncontrolled hemorrhagic shock and lung metastases at 2 weeks post-surgery.